If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(t + -2) + 6t = 9t + -7 Reorder the terms: -2(-2 + t) + 6t = 9t + -7 (-2 * -2 + t * -2) + 6t = 9t + -7 (4 + -2t) + 6t = 9t + -7 Combine like terms: -2t + 6t = 4t 4 + 4t = 9t + -7 Reorder the terms: 4 + 4t = -7 + 9t Solving 4 + 4t = -7 + 9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-9t' to each side of the equation. 4 + 4t + -9t = -7 + 9t + -9t Combine like terms: 4t + -9t = -5t 4 + -5t = -7 + 9t + -9t Combine like terms: 9t + -9t = 0 4 + -5t = -7 + 0 4 + -5t = -7 Add '-4' to each side of the equation. 4 + -4 + -5t = -7 + -4 Combine like terms: 4 + -4 = 0 0 + -5t = -7 + -4 -5t = -7 + -4 Combine like terms: -7 + -4 = -11 -5t = -11 Divide each side by '-5'. t = 2.2 Simplifying t = 2.2
| 8d+3=3d+33 | | 13=2-3x | | (M+3)(2m+5)=0 | | 7c-6=13 | | 1189=ax+by+z | | Y=2.5+3 | | -9-9=-27 | | 9(x-7)=-1.8 | | 6a=11 | | (5x+3)(x+2)=0 | | 2s-5=9 | | 3.3*9.3= | | g(-4)=5x-9 | | 10.6=2x-1 | | 3x-1=12.5 | | 2x+4=3x-s | | N(n+1)=0 | | 5+2(x-2)+3x=2(2x+1) | | p(x)=x^4-8x^3+14x^2-8x+13 | | x^2=7x-5 | | G(0)=5x-9 | | 2x+4=5x-9 | | 4x+5=75 | | -2=2x-6 | | K^2-16k+11=0 | | 4x+13=5x-3 | | (2r^3+r^2+r)/4r^2 | | 7x+18-6x^2+8x-7= | | 8x-11x=6 | | g(3)=5X-9 | | z5/2z-1/2/z1/3 | | -5*(-5)= |